A time-of-flight powder neutron diffraction study of non-stoichiometry in barium iridate BaIrO3-delta - Powell, A; Battle, P (1996)
Rietveld refinement of room temperature time-of-flight powder neutron diffraction data for a sample of BaIrO3-δ, prepared by slow cooling of polycrystalline single-phase material from 1223 K, was carried out in the space group C2/m; a = 9.9992(3) Å, b = 5.7490(1) Å, c = 15.1707(2) Å, β = 103.27(1)°. Refinement of oxygen site occupancy factors indicated that the material was almost ideally stoichiometric with a composition BaIrO2.94. Analogous refinement of data for a sample produced by rapidly quenching from 1223 K resulted in similar parameters; space group C2/m, a = 10.0010(4) Å, b = 5.7521(1) Å, c = 15.1747(3) Å, β = 103.26(1)°. Refinement of oxygen site occupancy factors indicated significant numbers of defects on the oxide sublattice corresponding to a composition BaIrO2.74. The distribution of these defects and their effect on the detailed structure of the phases are discussed.